15 years of zebrafish chemical screening - Rennekamp, Andrew J. (Curr Opin Chem Biol, 2014)
In 2000, the first chemical screen using living zebrafish in a multi-well plate was reported. Since then, more than 60 additional screens have been published describing whole-organism drug and pathway discovery projects in zebrafish. To investigate the scope of the work reported in the last 14 years and to identify trends in the field, we analyzed the discovery strategies of 64 primary research articles from the literature. We found that zebrafish screens have expanded beyond the use of developmental phenotypes to include behavioral, cardiac, metabolic, proliferative and regenerative endpoints. Additionally, many creative strategies have been used to uncover the mechanisms of action of new small molecules including chemical phenocopy, genetic phenocopy, mutant rescue, and spatial localization strategies.